Menstrual practices and hygiene: A study on Nepali adolescent girls of Assam, India - Barua, Pinky (Nepal Sociological Journal, 2025)
The Nepalis living in Assam (India) are mostly descendants of those who migrated or were transferred from Nepal to work in various sectors by the British. Now, Nepalis are basically working in agricultural fields and rearing animals. They have assimilated with the greater Assamese society and also have maintained their identity. The paper is about the study of women’s life and rituals related to women’s life in the Nepali pastoral society of Assam. In Assam, whether Hindu, Muslim, or Christian, they observe rituals related to menstruation, which are physical, social, or psychological. In my observation, the ritual related to menstruation in Nepali society has significance according to their religion, caste, and ethnicity. From the field, it reveals that these practices are related to the concept of purity and pollution. The paper shows that Nepali women, and especially adolescent girls, are reluctant to talk about menstruation and hygiene practices. The study is based on qualitative research, FGDs, and in-depth interviews to collect information. The study is conducted in the rural area to find out the basic challenges encountered by the Nepali adolescent girls during their menstrual days. The paper shows how poor menstrual hygiene can lead to school absenteeism.